Pendidikan Karakter Berbasis Sosial di MTI Tarusan Kamang dan Implikasinya Terhadap Masyarakat Jorong Babukik - Abdul Rahman‎; Monia, Fenny Ayu; Zurharfi, Zurharfi (Indonesian Research Journal on Education, 2023)
Education is an education that is very obligatory for every child because without character education children have difficulty socializing with the surrounding community, even if character education is not instilled in the children of MTI Tarusan Kamang from an early age, children will automatically have difficulties. understand the values of social knowledge or values that are appropriate to the social conditions of the local community. So what is the problem at this time is what are the factors that cause social-based character education and the implications for the Babukik community. So therefore the aim ofthe research is what are the things that make the children of MTI Tarusan included in the Jurong Babukik community. This study used a survey approach to interviews conducted with teachers teaching at MTI Tarusan Kamang, students taking part in the lessons, and the local community. With these interviews, we can see what causes the children of MTI Tarusan to have a connection with the Jorong Babukik community. With the interviews conducted, we can see the relationship between character and socialbased education and the implications for the Babukik community, namely that the MTI Tarusan is located in the area of 4 congregations or 4 jorongs, while the Halalang, Jorong Padang Kunyik, and Jorong Bansa.